PENGARUH MOTIVASI DAN SIKAP WIRAUSAHA TERHADAP KEPUTUSAN BERWIRAUSAHA WANITA DI KOTA JAMBI - Revia Setiani; dahmiri dahmiri; Sigit Indrawijaya (Jurnal Manajemen Terapan dan Keuangan, 2019)
This study aims to analyze the influence of motivation and attitudes of entrepreneurs to the decision of women entrepreneurship in the city of Jambi. The population in this study were women aged 15 years and over with the number 213.096 with 100 respondents. This type of research includes ex post facto research. This research is a correlational descriptive research. Data collection techniques used for primary data obtained from the distribution of questionnaires while for secondary data obtained from various library materials. Analyzer used in this research are, data quality test consist of test of validity and reliability test, multiple linear regression analysis, t test, f test and coefficient of determination test. The overall analysis was calculated using SPSS ver 15 program. The results showed that motivation variable (X1) had a significant effect partially on entrepreneurship decision. As for the entrepreneurial attitude variable (X2) had a significant effect partially on the decision of entrepreneurship. Motivation (X1) and entrepreneurship attitude (X2) had significant effect simultaneously to woman entrepreneurship decision in Jambi city.